Non-cognitive Support for Postgraduate Studies: A Systematic Review - Frantz, Jose; Cupido-Masters, Jill; Moosajee, Faranha; Smith, Mario R. (Frontiers in Psychology, 2022)
Retention of postgraduate students is a complex problem at higher education institutions. To address this concern, various forms of academic support are offered by higher education institutions to nurture and develop postgraduate students and the pipeline. The support provided to postgraduate students tends to emphasise academic support at times at the expense of psychosocial or non-academic support. Non-cognitive skills were underscored as integral to determining academic and employment outcomes and thus may need to be investigated more. This manuscript reports on an attempt to filter and consolidate the literature reporting on interventions for postgraduate students that include the development of non-cognitive skills. A systematic review was conducted using covidence systematic review software because it enabled a rigorous and replicable process for consolidating literature. The review was conducted at four levels as per the PRISMA guideline namely, identification, screening, eligibility and final summation. The filtration process attempted to answer the following research questions: 1) How are non-cognitive factors or skills defined?; 2) Which non-cognitive skills were included in support for postgraduate (Masters and Doctoral) students in the higher education setting?, and 3) How have non-cognitive skills been included in support interventions provided to retain postgraduate students? The primary finding was that the term non-cognitive was not used explicitly in the included studies to describe skills or factors supporting student retention. The discourse centred around support and social support as non-academic factors and skills. This suggested that non-cognitive skills were not seen as an integrated part of the postgraduate academic project or core learning outcomes.